Expression of the p53 protein and clinical and pathologic correlation in adenocarcinoma of the rectum - Jurach,Márcia Teresinha (2006)
BACKGROUND: p53 is a tumor suppressor gene that has been implicated in the pathogenesis of a wide range of tumors, including colorectal cancer. AIM: To evaluate the prognostic significance of p53 protein expression, and to correlate with clinical and pathologic variables as well as survival. PATIENTS AND METHODS: Immunohistochemical staining for p53 protein was performed in a series of 83 patients with rectal cancer with a follow-up of at least 5 years. RESULTS: Expression of nuclear protein was positive in 36 (43.4%) of the tumors. We found association between positive p53 and death, local recurrence, distant metastasis and overall recurrence and we also found association between p53 and death, local recurrence, metastasis and overall recurrence when analysis was adjusted to Astler-Coller stage and grade of differentiation. CONCLUSION: p53 immunoexpression has shown to be an independent prognostic factor in these series.